Knowledge, Attitude and Practices of Voluntary Blood Donation among Students of Rawalpindi Medical University. - Arshia Kanwal, Arshia Kanwal; Sarwat Saif, Sarwat Saif; Umair Ashfaq, Umair Ashfaq; Amjad Ali Raza, Amjad Ali Raza (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Each year more than 1.5 million pints of blood are collected In Pakistan. Among them 25% are volunteer donors, about 65% of the donation is by family or replacement while about 10% is from professional donors. The aim of this study was to determine knowledge, attitude, and blood donation practices among medical students of Rawalpindi medical university. This study also determined the reasons for not donating blood. Materials and Methods: This cross-sectional descriptive study was conducted in Rawalpindi medical university from January 2018 to June 2018. 300 students were enrolled by non-probability consecutive sampling. A structured questionnaire was designed and SPSS version 22 was used for data analysis. Results: Mean age of the respondents was 22±7 years. 269 (89.7%) of the participants knew their blood group. Among the respondents, 161(53.7%) knew minimum age for blood donation and 183 (61%) respondents had knowledge of weight requirement. 39 (13%) individuals have donated blood in the past .177 (59%) showed willingness to voluntarily donate blood in future Conclusion: Knowledge of blood donation among undergraduate medical students was found to be satisfactory. While the frequency of blood donation was not satisfactory. Majority of students showed the willingness to donate blood in the future. Keywords: Blood donation, medical students, blood group